Experimental Study and Mathematical Modeling of Metals Dissolution from LCD Boards in Na2S2O8 Environment. Issue 1 (2nd January 2017) - Popescu, Ioana-Alina; Varga, Tamás; Egedy, Attila; Fogarasi, Szabolcs; Ilea, Petru
Abstract : The current article aims to study the influence of pH, temperature, and oxidant concentrations on the dissolution process of metals from liquid crystal display (LCD) boards in a Na2 S2 O8 environment. The dissolution rate of metals is enhanced by the decrease of pH and increase of temperature and Na2 S2 O8 concentration. Based on the obtained results, a reaction mechanism was proposed and the reaction rate parameters (pre-exponential factor and activation energy) were determined. Kinetic analysis of the leaching process was performed in accordance with a shrinking core model. The activation energy was found to be 29, 924, 11, 871, 22, 434, and 38, 401 J/mol for Cu, Sn, Ni, and Pt, respectively, in a temperature range of 30°C–75°C, which was also an indication of the combined transport–chemical control. The experimental results were in good agreement with the simulated data and revealed that persulfate solutions are suitable reactants for metals leaching from LCD boards.